The moderating role of coping flexibility in reports of somatic symptoms among early breast cancer patients. (September 2022) - Dahabre, Rawan; Roziner, Ilan; Bentley, Gabriella; Poikonen-Saksela, Paula; Mazzocco, Ketti; Sousa, Berta; Pat-Horenczyk, Ruth; ,
Abstract: Objective: The current study assessed breast cancer patients' somatic symptoms during the first six months post diagnosis and examined the moderating role of coping flexibility (i.e., trauma-focused and forward-focused coping strategies) on the association between reported somatic symptoms three months after breast cancer diagnosis and somatic symptoms six months after diagnosis. Method and measures: An international sample of 702 women diagnosed with breast cancer from four countries (Finland, Israel, Italy, Portugal) completed self-reported questionnaires at three time points: at the time of diagnosis (M0), three months post diagnosis (M3), and six months post diagnosis (M6). The questionnaires included the coping flexibility scale and questions about demographics, medical data, and somatic symptoms. Results: The highest level of somatic symptoms was reported after three months post diagnosis (M3), as compared to M0 and M6. Both trauma-focused and forward-focused coping strategies moderated the relationship between somatic symptoms at M3 and somatic symptoms at M6. Conclusion: The findings highlight the importance of assessing somatic symptoms soon after breast cancer diagnosis and throughout the early phase of treatment. Coping flexibility can buffer the stability of the somatic symptoms during this initial phase. Highlights: Somatic symptoms start after a breast cancer diagnosis and reach a peak after three months. Coping flexibility mitigates the consistency of somatic complaints over the first six months. Coping flexibility contributes to improved quality of life in early-phase breast cancer patients. Screening somatic symptoms is recommended from diagnosis and throughout breast cancer treatment.